2022
DOI: 10.1111/lam.13729
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactobacillus paracasei N1115 on neonatal mice prevents the intestinal inflammation in adulthood

Abstract: Significance and Impact of the Study: Colonization and development of gut microbiota during early life plays a key regulatory role in the establishment of the host-microbial relationship, which was conducive to maintaining health throughout the adulthood life. This study was aimed to evaluate the protective effect from inflammatory bowel disease (IBD) in adulthood based on the early intervention of Lactobacillus paracasei N1115 (LP N1115). Results showed decreased severity of intestinal tissue injury, cell apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…To conclude, this study supports the notion that early postnatal nutrition is crucial for proper gut microbial colonization and that prebiotic fiber supplementation during this critical period of development might contribute to the improvement of the protective properties in altered nutritional environments. However, the consequences of such modifications for gut microbiota during postnatal development and in response to PNGR on later intestinal health and susceptibility to chronic intestinal diseases remain to be investigated [ 5 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, this study supports the notion that early postnatal nutrition is crucial for proper gut microbial colonization and that prebiotic fiber supplementation during this critical period of development might contribute to the improvement of the protective properties in altered nutritional environments. However, the consequences of such modifications for gut microbiota during postnatal development and in response to PNGR on later intestinal health and susceptibility to chronic intestinal diseases remain to be investigated [ 5 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, L. paracacei BD5115 promotes the proliferation of intestinal epithelial cells ( Qiao et al, 2022 ). Notably, neonatal administration of L. paracacei N1115 prevents intestinal inflammation in adulthood in mice ( Xun et al, 2022 ). A randomized controlled clinical trial has shown that oral administration of L. paracacei CBA L74-fermented formula could enhance the immune system, microbiota, and metabolome maturation in infants ( Roggero et al, 2020 ) and that L. paracacei BD5115 may help repair intestinal damage.…”
Section: Therapeutic Effects Of Probiotics On Ucmentioning
confidence: 99%
“…Lactobacillus paracasei N1115 (Lp N1115) was isolated from fermented milk products that have long been consumed by herders in Mongolia [24] and has potential probiotic properties such as the ability to promote intestinal development [25], improve intestinal symptoms [26], and regulate immunity [27]. However, the current research on Lp N1115 is mostly conducted on animals or in adults, and fewer trials are conducted on infants and young children.…”
Section: Introductionmentioning
confidence: 99%